2024
DOI: 10.3390/ani14060977
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effective Tissue Concentrations of Injectable Lidocaine and a Lidocaine-Impregnated Latex Band for Castration in Calves

Joseph A. Ross,
Steven M. Roche,
Kendall Beaugrand
et al.

Abstract: This study aimed to assess the effective tissue concentrations of the current standard of care for pain mitigation in calves during castration (injectable lidocaine) and to assess the ability of a lidocaine-loaded elastration band (LLB) to deliver effective concentrations into the scrotal tissue over time. This study comprised two different trials: (1) effective concentrations of injectable lidocaine in the scrotal tissue; and (2) the in vivo delivery of effective concentrations of lidocaine from LLBs placed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Previous work on the LLB used in the present study has demonstrated that these bands are able to effectively achieve therapeutic doses in the tissues studied over a 28-day period [21][22][23]. The goal of the present study was to compare castration and tail-docking efficacy between lidocaine-impregnated ligation bands and control bands under field conditions and to identify the benefits of pain control provided the LLB, with a focus on time to casting and ADG.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous work on the LLB used in the present study has demonstrated that these bands are able to effectively achieve therapeutic doses in the tissues studied over a 28-day period [21][22][23]. The goal of the present study was to compare castration and tail-docking efficacy between lidocaine-impregnated ligation bands and control bands under field conditions and to identify the benefits of pain control provided the LLB, with a focus on time to casting and ADG.…”
Section: Discussionmentioning
confidence: 97%
“…Control bands showed an increase in ADG between d 14 to 21 following castration and tail docking compared to LLB-treated animals. Other studies have noted that, in the absence of analgesia, a reduction in feeding behavior and growth occurs over the subsequent days following the procedure; however, compensatory growth in the weeks following the procedure occurs, as most of the pain has diminished from the tail and scrotum site [18,23]. Although compensatory weight gain occurs in control lambs, it is possible that carcass quality (fat vs. lean muscle and muscle development) may be influenced [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations